Variação no canto de anúncio de Dendropsophus cruzi (Pombal & Bastos,1998) (Anura: Hylidae) - Tessarolo, Geiziane (2010)
The advertisement call of anurans contains spectral and temporal information important for specific recognition, beside relevance in social organization and attraction of females. The variation in features call has been received attention because their importance in breeding behavior, and implications for the recognition of conespecifics in multiple levels of social organization. The objective of this study is to investigate patterns of variability in the acoustics properties of the advertisement call of Dendropsophus cruzi in different levels: individual, population and specific, in ten populations of state of Goiás. The following acoustic variables were analyzed: call repetition rate, duration of call, number of pulses, duration of pulse and dominant frequency. The acoustics parameters weret influenced as for temperature as for rostrumcloacal length (CRC), and presented different variability coefficients, within-male and among-male being the variability among-male greater than the variability within-male. The dominant frequency is the property of greater potential for use in the specific recognition and also is the characteristic that best discriminates populations. The geographic distance did not predict the differences found in the call. However, geographic cline patterns was found for duration of call, call repetition rate and CRC. The differences among populations can be due to local selective pressures as environmental and social structure of the chorus. The decreases of CRC to the north reflect the gradual change in the temperature in the same sense, influencing the development and growth rates, with smaller individuals. On the other hand, the increase of the temporal characters of call occur for increase the loss attractiveness caused by the high dominant frequency imposed by the smallest size of the body.